The Effectiveness of Contextual Teaching and Learning (CTL) in Improving Cognitive Learning Outcomes on Bench Work Practice - Galih TriLaksono; Khoirul Huda; Muhammad Khumaedi; Septian Eko Cahyanto; Kriswanto Kriswanto; Andri Setiyawan (Jurnal Pemberdayaan Masyarakat, 2025)
This study examines the contextual teaching and learning (CTL) model's effectiveness in improving cognitive learning outcomes of vocational education students. Using a pretest-posttest quasi-experimental design, this study involved 60 tenth-grade mechanical engineering students, divided equally into control and experimental groups. The experimental group received the CTL learning model treatment, while the control group used conventional learning methods. A 20-item multiple-choice test based on Bloom's Taxonomy was used to measure students' cognitive learning outcomes. Instrument validation showed good content validity (Aiken's V=0.714- 1.00) and obtained good reliability results as well (ICC=0.730). The experimental group received a higher average post-test score (89.17) compared to the control group (75.83), with the acquisition of N-Gain values in the experimental group (0.7427) and control group (0.4013), with statistical analysis showing a significant difference (p0.05). These findings indicate that CTL effectively improves basic understanding and critical thinking skills. This study supports the integration of CTL into vocational education systems aligned with international priorities of competency-based learning and workforce readiness. This study provides empirical evidence that CTL can improve learning outcomes and equip students with critical thinking skills.